If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 6(x + -9) + -5 Reorder the terms: -2 + 3x = 6(x + -9) + -5 Reorder the terms: -2 + 3x = 6(-9 + x) + -5 -2 + 3x = (-9 * 6 + x * 6) + -5 -2 + 3x = (-54 + 6x) + -5 Reorder the terms: -2 + 3x = -54 + -5 + 6x Combine like terms: -54 + -5 = -59 -2 + 3x = -59 + 6x Solving -2 + 3x = -59 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -2 + 3x + -6x = -59 + 6x + -6x Combine like terms: 3x + -6x = -3x -2 + -3x = -59 + 6x + -6x Combine like terms: 6x + -6x = 0 -2 + -3x = -59 + 0 -2 + -3x = -59 Add '2' to each side of the equation. -2 + 2 + -3x = -59 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = -59 + 2 -3x = -59 + 2 Combine like terms: -59 + 2 = -57 -3x = -57 Divide each side by '-3'. x = 19 Simplifying x = 19
| 12-2d=2 | | 10(4s+6)-40= | | y=x^2-7x-18 | | 20x^2+14x-10=0 | | y=-x^2-7x-18 | | 5(n+19)=200 | | 5(n+19)=20 | | y=-x^2-10x-25 | | 4x^2+1=101 | | 3(2r+5)-7= | | y=5x^2+25x | | 10x+12-9-7x+4x=31 | | 5x-12+7=7x+25 | | 3x-22+x=6+2x | | 12x-4=3x+32 | | -(q-2+6r)+2= | | 3+2x=5x-9 | | 2(x-1)=x+7 | | -(r-3-7p)+3= | | -(5x+2)= | | tgx-1=0 | | 3x+(-x)+2(-x)+8=2(-x) | | -4(1-2m+n)+4= | | 80-19x=20-4x | | 3a-12+18+2=10-5a | | 4x=2(x+8) | | -4(4+2p+5)+16= | | p+[0.5p+3]=21 | | 6a+5a+3a+2b= | | 5x^2+2=502 | | 6x=20-4x | | 12x*22=12 |